An Extrapulmonary Tuberculosis Patient with Deep Vein Thrombosis: A Case Report - Rupak Chatterjee; Sumanta Sinha; Kumkum Sarkar; Debananda Gonjhu; Sekhar Pal; Netai Pramanik (Advanced Concepts in Medicine and Medical Research Vol. 1, 2023)
Tuberculosis has many mechanisms that may lead to hypercoagulable state and can lead to thromboembolic complications. It may be a potentially life-threatening condition. The physician’s awarness of this disease condition is important to an early diagnostic suspicion and prompt treatment to prevent fatal outcomes. Among the various complications reported to be caused by tuberculosis (TB), throm- bogenic potential is a rare entity. Here, we report a case of colonic tuberculosis in a 30-year-old male who developed left upper limb deep vein thrombosis (DVT). Ruling out other possible causes of DVT and improvement of the affected limb with antitu- bercular drugs led to conclusion that DVT was most probably due to TB.